A simple and efficient control allocation scheme for on-ground aircraft runway centerline tracking. (February 2020) - Sadien, Edouard; Roos, Clément; Birouche, Abderazik; Carton, Mathieu; Grimault, Christophe; Romana, Louis Emmanuel; Basset, Michel
Abstract: To achieve a high performance level during ground operations, the lateral dynamics of an aircraft must be controlled using all available actuators (rudder, nose-wheel steering system, engines and brakes) and under various constraints, which gives rise to a challenging allocation problem. To address this issue, a simple yet accurate design-oriented on-ground aircraft model is first developed. It takes into account the effects of aerodynamics, thrust and tire–ground interactions, both laterally and longitudinally, and for several runway states. It is validated on a high-fidelity Airbus simulator and a complete set of numerical values representative of a commercial aircraft is given, as well as design objectives, so as to provide the control community with a challenging benchmark. After an extensive literature review and an evaluation of the pros and cons of many existing control allocation techniques, a novel and easily implementable algorithm is then developed, which meets actuator and implementation constraints. It automatically manages the trade-off between two antagonistic objectives, namely minimizing the control effort and attaining the maximum virtual control. Its validation on both the design-oriented model and the high-fidelity simulator shows promising results.